Pavement Condition Index (PCI) Analysis In Measuring Road Damage Levels and Its Effect on Vehicle Speed in Lembar-Sekotong-Lombok Barat Road Segment - Haryati, Norma Widya; Mahendra, Made Mahendra; Murtiadi, Suryawan (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
As a means of transportation, the position and role of the road network in essence concern the livelihoods of many people to maintain the sustainability and service quality of these roads. If the road section is damaged, it will have a significant impact on the condition of the traffic flow. Many road damages occur due to the high use of the road which causes a high volume of vehicles, overloaded vehicles, rainwater runoff or poor drainage systems and others. The Sheet-Sekotong-Pelangan road section is a provincial road section located in West Lombok Regency, NTB. This road segment has been damaged in several road segments and disrupted traffic flow so it requires handling. In this regard, the purpose of this study is to determine the level of road damage using the Pavement Condition Index (PCI) method and to determine the effect on vehicle speed and to find recommendations that are appropriate to the level of road damage. This study includes a visual survey to determine the condition of road damage and vehicle speed. The analysis used to determine the effect of road damage on vehicle speed is Simple Linear Regression. The results of the analysis show that the R square value is 0.893, which means that road damage has an influence on vehicle speed of 89.3%. Regression model y (vehicle speed) = 9.012 + 0.581x (PCI), which means that if the PCI 9.012 variable increases by 1 unit or 1%, the vehicle speed will increase by 0.581 units or by 58.1%. The lower the PCI value, the slower the vehicle speed will be. Conversely, the greater the PCI value, the faster the vehicle speed.